INFLUENCE OF SHAIVISM ON THE MAURYAN EMPIRE - Manoj Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Shaivism, one of the major branches of Hinduism, considers Lord Shiva as the supreme God. This paper explores the historical and cultural significance of Shaivism during the Mauryan Empire (c. 322–185 BCE), an era of political unity and cultural progress in ancient India. The Mauryan emperors, especially Emperor Ashoka, played a key role in religious tolerance and the consolidation of various philosophical traditions, including Shaivism. Through archaeological evidence, literary sources, and historical accounts, this research highlights the influence of Shaivism on art, architecture, and social values in the Mauryan Empire. The findings of this research underscore the enduring legacy of Shaivism in shaping the religious landscape of India.